Assessing the Impact of Project-Based Learning on Students’ Writing Skills: A Pre-Experimental Study - Nurul Hakimah (Universitas Muhammadiyah Kalimantan Timur, 2023)
This pre-experimental study examines the effectiveness of project-based learning (PBL) on the writing skills of Class 9D students at SMP Negeri 48 Surabaya during the academic year 2022/2023, specifically focusing on procedure text. The goal is to enhance students’ writing abilities, particularly in the area of procedural writing. The study involves a single group of 42 students from Class 9D, selected through convenience sampling. The intervention consists of implementing PBL, where students actively engage in hands-on activities, collaborative projects, and authentic writing tasks related to procedure texts. The intervention period is designated for active student participation in procedure text-based projects. Pre-test and post-test assessments evaluate the impact of PBL on writing skills, considering criteria such as organization, clarity, coherence, and language proficiency. The analysis compares the writing scores from these assessments. The findings aim to provide insights into the effectiveness of PBL in enhancing students’ writing skills within the context of procedure text. Implications of the study suggest that implementing PBL strategies in writing instruction offers significant benefits to students. Authentic tasks and hands-on experiences foster creativity, critical thinking, and problem-solving skills. Educators can incorporate PBL into procedure text instruction based on these findings. Integrating PBL strategies into the curriculum enhances students’ writing skills. Providing professional development opportunities assists teachers in designing and implementing effective PBL activities. Further research is needed to explore the long-term effects of PBL on writing skills across different genres and grade levels.